Effects of Low-Flux and High-Flux Dialysis Membranes on Erythropoietin Responsiveness in Hemodialysis Patients - Walid A. R. Abdelhamid; Mohamed M. Soliman; Ayman R. A. El-Hameed (International Journal of Nephrology)
Background. Chronic kidney disease (CKD) is often accompanied by anemia. High-flux membranes contribute to a reasonable removal of uremic toxins which cause anemia in CKD. Inadequate data have described the efficiency of high-flux dialysis in promoting erythropoietin responsiveness in CKD patients in the Middle East. This study was conducted to compare the efficiency of maintaining high-flux hemodialysis versus low-flux dialysis for ≥1 year in promoting erythropoietin responsiveness and to show the factors associated with erythropoietin hyporesponsiveness in Arab chronic hemodialysis patients. Methods. It was a retrospective cohort study that involved 110 subjects who were categorized into group 1 (50 patients receiving low-flux dialysis) and group 2 (60 patients receiving high-flux dialysis). History taking, examination, and laboratory investigations were conducted for all patients every 3 months from January 2021 to January 2022. Results. Group 2 had significantly higher weight and body mass index than group 1 but lower cholesterol and intact parathyroid hormone levels than group 1. Erythropoietin resistance index levels did not differ between the two groups upon repeated measures over a 1-year follow-up. Significant risk factors for erythropoietin hyporesponsiveness on multivariate analysis were lower weight (Odds ratio (OR): 0.966; 95% Confidence interval (CI): 0.94–0.992; p=0.011), longer hemodialysis vintage (OR: 1.172; 95% CI: 1.036–1.325; p=0.012), lower hemoglobin levels (OR: 0.531; 95% CI: 0.362–0.779; p=0.001), and higher neutrophil-to-lymphocyte ratio (OR: 2.436; 95% CI: 1.321–4.493; p=0.004). Conclusion. High-flux dialysis was not superior to low-flux dialysis in improving erythropoietin responsiveness.